2007
DOI: 10.1073/pnas.0610832104
|View full text |Cite
|
Sign up to set email alerts
|

Diazonamide toxins reveal an unexpected function for ornithine δ-amino transferase in mitotic cell division

Abstract: We have studied a naturally occurring small-molecule antimitotic called diazonamide A. Diazonamide A is highly effective at blocking spindle assembly in mammalian cell culture and does so through a unique mechanism. A biotinylated form of diazonamide A affinity purifies ornithine ␦-amino transferase (OAT), a mitochondrial enzyme, from HeLa cell and Xenopus egg extracts. In the latter system, the interaction between diazonamide A and OAT is regulated by RanGTP. We find that specific OAT knockdown in human cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
92
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 24 publications
0
92
0
2
Order By: Relevance
“…7a) (Oda et al 2003;Wang et al 2007;Ong et al 2009). However, besides matrix binding, a large number of nonspecific proteins are from low affinity ligand binding or indirect binding to target proteins.…”
Section: Negative Control Experimentsmentioning
confidence: 98%
See 1 more Smart Citation
“…7a) (Oda et al 2003;Wang et al 2007;Ong et al 2009). However, besides matrix binding, a large number of nonspecific proteins are from low affinity ligand binding or indirect binding to target proteins.…”
Section: Negative Control Experimentsmentioning
confidence: 98%
“…In order to control for these interactions, one may use a ''negative ligand'', an analog structurally similar but is inactive in the corresponding cellular assay (Fig. 7a) (Oda et al 2003;Wang et al 2007;Li et al 2014a). However, caution should be taken when choosing the ''negative ligand'', since it is possible that an inactive analog may be still able to physically bind the target but with reduced affinity so that it does not exhibit the same cellular activity as the positive compound.…”
Section: Negative Control Experimentsmentioning
confidence: 99%
“…Although AB-5 functions as an antimitotic, both in vitro and in vivo, Wang et al (17) have shown that it does so through a unique mode of action involving a heretofore unrecognized role for OAT in cell division (17). Mice deficient in OAT The AB-5 metabolite was generated by incubation of AB-5 with human S9 protein for 4 h and then fractionated by HPLC on a C18 column.…”
Section: Analysis Of Ab-5 Pharmacokinetics and Metabolismmentioning
confidence: 99%
“…Notably, however, studies by CruzMonserrate et al (15) indicated that diazonamide A does not compete with vinblastine or colchicine for tubulin binding. In fact, our own studies have shown that neither biotinylated nor radiolabeled congeners of the natural product interact specifically with purified tubulin in vitro, raising the possibility that the compound does not act by binding directly to tubulin (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation